Gambaran Kualitas Hidup Kesehatan Remaja di Kota Bitung pada Masa Pandemi Covid-19 - Liang Kevin Arsastha; Crifianny Praysilia Wenas (Pusat riset dan Inovasi Nasional, 2025)
Health-Related Quality of Life (HRQoL) in adolescents is a crucial indicator for measuring the impact of the Covid-19 pandemic on their physical, psychological, social, and environmental well-being. This study aimed to describe the health-related quality of life of junior and senior high school students in Bitung City during the pandemic. The research was conducted quantitatively with a cross-sectional approach, involving 423 students. The instrument used was the WHOQOL-BREF, modified for an adolescent population. The results showed that the majority of respondents had a moderate quality of life (70.4%), with an average total score of 60.0. The highest domain score was in the psychological aspect (64.69), and the lowest was in physical health (51.74). These findings reflect the significant impact of the pandemic on the quality of life of adolescents, particularly in physical and social aspects, and emphasize the need for integrated interventions for post-pandemic recovery.